Preeclampsia – a risk factor for osteoporosis? Analysis of maternal Sclerostin levels and markers of bone turnover in patients with pre-eclampsia. (August 2014) - Wild, Julia; Pateisky, Petra; Küssel, Lorenz; Huf, Wolfgang; Ott, Johannes; Haslinger, Peter; Knöfler, Martin; Zeisler, Harald
<x xml:space="preserve">Abstract</x> Introduction: The role of preeclampsia (PE) in affecting bone metabolism could not be clarified in the past years. Recently Sclerostin, a new marker of bone metabolism which is known to have an inhibitory effect on bone formation causing osteoporosis, was discovered. Objective: To investigate serum levels of Sclerostin and markers of bone turnover in women with normotensive pregnancies and pregnancies complicated by PE. Methods: In this prospective study we enrolled 22 women with PE and 22 healthy pregnant women to observe serum levels of carboxyterminal propeptide of type I collagen (PICP), cross-linked carboxyl terminal telopeptide of the type I collagen (ICTP), calcium, phosphate, 25-hydroxyvitamin D and parathyroid hormone. In 16 preeclamptic and 16 healthy pregnant women, serum Sclerostin levels were analyzed. Results: Serum levels of Sclerostin (mean ± standard deviation: healthy 10.5 ± 8.1 pmol/l versus PE 11.5 ± 9.4 pmol/l, p = 0.768), ICTP (healthy 0.3 ± 0.2 ng/ml versus PE 0.4 ± 0.1 ng/ml, p = 0.462), PICP (healthy 59.9 ± 49.9 ng/ml versus PE 89.0 ± 62.0 ng/ml, p = 0.094), phosphate (healthy 1.1 ± 0.2 mmol/l versus PE 1.2 ± 0.4 mmol/l, p = 0.162) and parathyroid hormone (healthy 26.9 ± 14 pg/ml versus PE 35.3 ± 17.6 pg/ml, p = 0.08) showed no significant differences between the groups. Significantly lower serum calcium (healthy 2.3 ± 0.1 mmol/l versus PE 2.2 ± 0.2 mmol/l, p < 0.005) and serum 25-Hydroxyvitamin D (healthy 39.3 ± 16.7 nmol/l versus PE 23.9 ± 16.9 nmol/l, p < 0.005) were observed in preeclamptic women. Conclusion: Pregnancies complicated by PE show no signs of high bone turnover and may not lead to a higher risk of osteoporosis in later life.